Hackathon as an active learning format in higher education institutions - Sergeyeva Olena; Pavlova Larysa; Leshnyova Natalia (Scientific notes of the pedagogical department, 2023)
The article is devoted to the topical issue of foreign language teaching methods in higher educaton institutions - the creation of a modern methodological framework for the educaton and training of future specialists in any ﬁeld of professional actvity.Therefore, we consider changes in methodological approaches in teaching to be appropriate and necessary. An analysis of scientific research on the above-mentioned problem is presented in the article and the need to find the latest formats for creating a methodical base during the professional training of a future specialist who is ready to work in the conditions of modern changes and new standarts is emphasized. The purpose of the article is to show the possibilities of using a hackathon as an effective learning format that promotes the development of critical thinking in higher education students, which in turn meets the requirements of the modern format of the professional training of a future specialist in any field.